The Influence of Environmental Geographical Factors on the Epidemiological Dynamics of Tuberculosis Disease in East Java - Novarina Sulsia Ista'in Ningtyas; Sukri Nyompa; Erman Syarif (LaGeografia, 2026)
Tuberculosis (TB) is an infectious disease with a spread that is influenced by the interaction between factors of the physical, socio-economic, and geographical characteristics of the region. This study aims to analyze the influence of environmental geographical factors on disease epidemiological dynamics in East Java. The research method uses a systematic literature review based on Preferred Reporting Items for Systematic Reviews and Meta Analyses with literature obtained from PunMed, ScienceDirect, Goggle Scholar and Garuda databases with a period of 2020-2026. An analysis was carried out on articles that discussed physical, socio-economic, and spatial analysis of TB epidemiology. The results showed that population density, poor home ventilation, high humidity, low environmental sanitation, poverty, urbanization, and limited access to health services had an effect on the increase in TB cases. The level of population density between urban and rural areas has an influence on the prevalence of TB. Spatial analysis showed that the pattern of TB distribution formed clusters in urban areas and areas with high population mobility. The environmental geography approach and spatial analysis are considered effective by identifying high-risk areas so that they can support the government in an integrated and sustainable region-based TB control strategy.